Interview with Piet J. Naudé - Martin Laubscher (Acta Theologica)
From text: Piet Naudé studied at the University of Stellenbosch where he completed a BA with Hebrew and Philosophy as majors. He furthered his studies in Philosophy and completed both an Honours and Masters degree, the latter in theories of social justice, with Willie Esterhuyse as study leader. He completed the standard postgraduate theological studies (B.Th. and Licentiate) for admission as pastor of the Dutch Reformed Church. For his doctoral studies in dogmatics under Willie Jonker, he spent a year in Utrecht, The Netherlands. His thesis explored the relation between theory and practice in Latin-American Liberation Theologies and the work of Johann Baptist Metz. As Humboldt scholar, he later built a special academic relation with Michael Welker in Heidelberg (Germany) and with the Centre for Theological Inquiry at (USA).